Teoria dos Grafos no ensino médio: aplicações em problemas de trânsito - Della Torre, João Paulo Gonçalves (2018)
This work, explores through the methodologies: Problem Solving and Mathematical Modeling, concepts of Graph theory in the second year of the High School of a State School. The concepts developed here in a contextualized way, aim to lead the students to experience con- tent not present in the curriculum, but that can be used to explain and solve everyday problems.